(untitled) (Bangladesh Journal of Microbiology, 2016)
The present study was carried out to develop a sustainable production medium using locally available cheap raw materials for biopesticide production by Bacillus thuringiensis subsp. kurstaki (Btk) HD-73. In submerged fermentation (SmF) condition, the conventional Luria-Bertani (LB) medium which was enriched with nitrogen source (10% defatted soybean meal) supported 28.57% sporulation and 125% endotoxin increase over LB (alone). The effect of cystine on sporulation and endotoxin synthesis was highly pronounced in LB-soybean medium (LBS) with a range of 19.54% and 131.35% higher endotoxin yield respectively in SmF condition. While basal salts supplemented in soybean-cystine (SMc) medium, it resulted in 7.65% endotoxin yield compared to LB-soybean-cystine (LBSc) medium. Addition of molasses balanced the C: N ratio in the SMc medium thus helping 84.85% higher endotoxin synthesis after 24 hours fermentation. Substitution of basal salts with cost effective sea water yielded about 19.27% less endotoxin. The optimum medium thus obtained consisting of soybean extract-molasses-cystine with sea water was used in 3.0 L bioreactor cultivation for endotoxin synthesis by Btk HD-73 under 30% saturation of dO2 through cascade of agitation and aeration. The production rate obtained was 1.67 fold higher in bioreactor than in shake flask culture. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 1-6